The living condition in the historic city center of Southeast Asia: the case of Penang in Malaysia - Karim, A.H.M Zehadul (Serials Publications, 2010)

(untitled)
This paper on the living condition in the City Center of Southeast Asia is an analysis of the restructured way of life and living in two centrally located and historically significant streets of Penang City in Malaysia. From historical point of view, these locations represent one of the oldest settlement areas of Penang, having exposure to business privileges and commercial facilities. The study aims at understanding the better effects of housing located in these historically significant inner city centers as they undergo transformation in response to the recent urban growth and socio-economic development. The newly developed urban areas in the city had brought massive changes to its specific spatial characteristics as well as in the community life of these areas as they have now been purposefully reorganized. It has been observed that with the expansion of cities, the new generations have now the tendency to move to the new localities as they provide them with modern facilities and more suitable living environment. It now therefore, becomes a vital issue to explore as to what happens to the existing buildings and the communities living in them that lie in the path of development. Based on our empirical data from a selected sample household survey, the paper however is not so much an attempt to evaluate their importance as historic monuments but more to examine them a segment of the inner city life. This neighborhood then will display the distinct traditional character of its housing system alongside of the new and modern forms and functions that are allowed to grow out from around them. It is often argued that old neighborhoods should continue to be preserved as they stand as signposts and reflect our cultural continuity from the past through present to the future. By carefully depicting the peculiarities of neighborhood roles that shape their differential way of life in which all peoples of varying backgrounds and social standing do participate and interact each other, we should be able to decide whether these neighborhoods are appropriate for preservation.